Awareness and Perception of Healthcare Providers about Proxy Consent in Critical Care Research - Rania Mahafzah; Karem H. Alzoubi; Omar F. Khabour; Rana Abu-Farha (Critical Care Research and Practice)
Objective. Proxy consent respects patients’ autonomy when they are incapable of providing consent for research participation. Healthcare providers need to understand the ethical regulations and practices relevant to the proxy consent process. Thus, this study aimed to assess the knowledge and attitudes of healthcare providers about research proxy consent in the ICU setting. Methods. A cross-sectional survey-based design was used in the study. Study participants were resident and specialist physicians, registered nurses, and registered pharmacists from ICU units in Jordan. Participants were asked to fill out a questionnaire developed to assess their knowledge and attitudes towards informed proxy consent for research studies conducted at the ICU. Results. In this study, 145 healthcare providers completed the study questionnaire. The healthcare providers agreed that the purpose of the proxy consent is to inform the participants about the potential benefits (66.9%) and risks (66.9%) related to the research to study and respect patient's autonomy (44%), to discuss alternative options (62.1%), and to protect the researchers from any litigation (84.1%). Regarding the assessment of proxy consent, 65.5% of respondents believed that relatives are considered as an authorized legal representative for an informed consent decision on behalf of their ICU patients (65.5%) as they are knowledgeable about patients' values and preferences and have the desire to provide the necessary help. Respondents also agreed that the informed consent process should explain research protocols and procedures (76.6%), therapeutic alternatives (84.1%), potential benefits (41.4%), and potential risks (44.1%) and that participation in the research is voluntary (66.9%). No significant differences in the responses were found among different groups of healthcare providers. Conclusion. The majority of healthcare providers had inadequate awareness about the ethical aspects regarding the informed proxy consent process. Providing training regarding the informed consent process can improve the quality of the proxy consent process in clinical research studies in the ICU setting.